Study of wave processes at the initial stage of RF-heating in the Uragan-3M torsatron - Pashnev, V.K.; Tarasov, I.K.; Sitnikov, D.A.; Sorokovoy, E.L.; Tsybenko, S.A.; Chechkin, V.V.; Grigor’eva, L.I.; Beletskii, A.A.; Kasilov, A.A. (Вопросы атомной науки и техники, 2017)
The study of wave processes occurring during the initial stage of RF plasma heating in the Uragan-3M torsatron was performed with using movable magnetic and electric probes. The heating was carried out by the frame antenna. The electric probe allowed to register changes of the plasma density profile, while the magnetic probes measured amplitude and phase shifts between all magnetic field components at different points over the plasma column cross-section. The frequency spectrum of magnetic field fluctuations contains the main frequency that coincides with the RF oscillator frequency and higher harmonics. The amplitude of the 2nd harmonic in this mode can be compared with the amplitude of the basic harmonic.